Numerical methods for chemical engineers : using Excel, VBA, and MATLAB - Law, Victor J. (CRC Press, 2013)
"Preface This book has been written using notes developed for the course Numerical Methods for Chemical Engineers at Tulane University. The author has written two previous textbooks; one on FORTRAN programming and one using the language Pascal. On a personal note, when I completed the Pascal book I asked my wife to break my fingers if I ever decided to write another book! Well, that was a long time ago and having been granted a sabbatical leave to write this book, my wife decided that she would look the other way. While there are many textbooks whose title would indicate that they are suitable for the course Numerical Methods for Chemical Engineers, every one that has been tried has been a failure in one way or another. Either they were too elementary and the applications and problems were not ideal or they did not offer instruction in Excel and Visual Basic for Applications (VBA). This led to the development, over a 5 year period, of detailed notes to be used in place of a textbook. These notes have been enhanced and put into textbook form to produce the present book. The primary reason for using Excel is that it is generally available software and it comes with every computer system (both PC and Mac) with Microsoft Office installed. VBA is a programming environment that comes with Excel and greatly enhances the capabilities of basic Excel spreadsheets. It is available on systems running Microsoft operating systems and Mac OS. Beware, however, that VBA is available only on the latest (2011) version of Microsoft Office for the Mac. Other programming software systems that are often used in chemical and biomolecular engineering numerical methods courses are the following:"--Vydavatelská anotace
Keywords: numerické metody; chemické inženýrství; Microsoft Excel (software); Microsoft Visual Basic (programovací jazyk); MATLAB (software); numerical methods; chemical engineering; Microsoft Excel; Microsoft Visual Basic; MATLAB; učebnice vysokých škol; textbooks (higher)